Law as a Means of Supply Chain Rural Modernization and Development Management in Indonesia during Reformation Era (Case Studies in Villages in West Java Province) - Nandang Alamsah Deliarnoor; Utang Suwaryo; Yusa Djuyandi (International Journal of Supply Chain Management, 2020)
Could law possibly be a means of supply chain rural modernization and development in Indonesia? As a comparison, South Korea with its saemaul undong is capable of developing supply chain rural areas well. Could Indonesian legal system, which is comparable to South Korea’s saemaul undong in terms of significance, serve as a means of modernizing and developing the supply chain rural areas? It is intriguing, considering legal issues, not only concern on legislation materials but also the legal structure and legal culture of the society. Therefore, this paper describes and analyzes the legal substance side of the village, its legal structure and culture in carrying out the role of modernizing and reforming the village. The results of the study revealed that legal modernization as a means of village development have been carried out in several villages in Indonesia especially West Java, however this condition was also driven by an increase in the capacity of the apparatus to form village regulations and promulgation in village sheets.